High-Resolution Carbonate System Dynamics of Netarts Bay, OR From 2014 to 2019 - Fairchild, William; Hales, Burke (Frontiers in Marine Science, 2021)
Netarts Bay is a shallow, temperate, tidal lagoon located on the northern coast of Oregon and the site of the Whiskey Creek Shellfish Hatchery (WCSH). Data collected with an autonomous continuous flow-through system installed at WCSH capable of high-resolution (1 Hz) partial pressure of aqueous CO2 (pCO2) and hourly total dissolved inorganic carbon (TCO2) measurements, with combined measurement uncertainties of <2.0% and 0.5%, respectively, is analyzed over the 2014-2019 interval. Summer upwelling, wintertime downwelling, and in-situ bay biogeochemistry represent significant modes of the observed variability in carbonate system dynamics. Summer upwelling is associated with large amplitude diel pCO2 variability, elevated TCO2 and alkalinity, but weak variability in salinity. Wintertime downwelling is associated with bay freshening by both local and remote sources, a strong tidal signature in salinity, TCO2, and alkalinity, with diel pCO2 variability much less amplified when compared to summer. Further, analysis of alkalinity-salinity relationships suggests multiple water masses inhabiting the bay during one year: mixing of end-members associated with direct precipitation, coastal rivers, southward displacement of the Columbia River plume, California Current surface and deep upwelled waters. The importance of in-bay processes such as net community metabolism during intervals of high productivity are apparent. These direct measurements of pCO2 and TCO2 have proved useful to local hatchery owners who have monitored intake waters following historic seed-production failures related to high-CO2 conditions exacerbated by ocean acidification.